Representativeness in the Eyes of the Citizen: Impact of Balanced Citizenship on the Perceived Representativeness in Participatory Governance - Lee, Junesoo; Choi, Heungsuk; Han, Seungjoo (International Journal of Public Administration, 2021)
Representativeness is one of the keys to the legitimacy of participatory governance. However, such representativeness might be in the eye of the beholder due to various definitions of, and criteria for, representativeness. This study aims to explore how citizens perceive the representativeness of their representatives and the reasons behind those perceptions. Based on a survey of 2,000 citizens in South Korea, the findings indicate: (1) the maturity of citizenship (i.e., balancing tolerance and participation) significantly influences citizens’ perceptions of the representativeness of public affairs participants, and (2) this pattern of perceived representativeness does not vary according to the representativeness type (i.e., stake, stance, service, specialty, sovereign, and socio-econ) and domain (i.e., community, corporates, and government). The findings imply (1) the existence of four distinct groups of citizens–considerate reformer, reserved endurer, silent groaner, and active grumbler–and (2) the four groups of citizens are predictors of perceived representativeness.